Social infrastructure, social cohesion and subjective wellbeing - Renee Zahnow (Wellbeing, Space and Society)
Neighborhood physical places that bring people together, referred to as social infrastructure, form the foundation of communities. Studies suggest that by facilitating social encounters, social infrastructure can enhance sense of social cohesion and belonging and may also improve subjective wellbeing. Yet the extent to which wellbeing benefits are mediated through increased social cohesion and belonging is less understood. Drawing on data collected in March 2022 from a nationally representative sample of 1000 Australian adults aged over 18 years, we use mediated regression analysis to examine the extent to which the link between social infrastructure and subjective wellbeing is mediated by perceived social cohesion and belonging. Our findings reveal that social cohesion and belonging partially mediate the relationship between proximate social infrastructure and wellbeing. Our findings go beyond previous studies that note the importance of walking or greenspaces for social interaction and cohesion to demonstrate that social and wellbeing benefits can be accrued across a suite of ordinary neighborhood places when the social context is perceived as cohesive. The results highlight the capacity for ordinary places such as shops and cafes to contribute to social cohesion during everyday activities and facilitate subjective wellbeing by satisfying the basic human need to belong.